Influence of Cytochrome P450 2C19 Genotype on Helicobacter pylori Proton Pump Inhibitor-Amoxicillin-Clarithromycin Eradication Therapy: A Meta-Analysis - Morino, Yuko; Sugimoto, Mitsushige; Nagata, Naoyoshi; Niikiura, Ryota; Iwata, Eri; Hamada, Mariko; Kawai, Yusuke; Fujimiya, Tatsuhiro; Takeuchi, Hironori; Unezaki, Sakae; Kawai, Takashi (Frontiers in Pharmacology, 2021)
Background: Proton pump inhibitors (PPIs) are the first-line treatment for acid-related diseases. The pharmacokinetics and therapeutic efficacy of PPIs, however, are influenced by genetic factors such as variants in genes encoding drug-metabolizing enzymes (e.g., cytochrome P450 2C19 [CYP2C19]) and drug transporters. We performed a meta-analysis to evaluate the influence of CYP2C19 genotype and PPI class on the cure rate of PPI-containing Helicobacter pylori eradication therapy. Methods: Randomized control trials (RCTs) investigating cure rates using a PPI-amoxicillin-clarithromycin regimen among different CYP2C19 genotypes through May 2021 were included. Results: A total of 25 studies (5,318 patients) were included. The overall eradication rate in the intention-to-treat analysis was 79.0% (3,689/4,669, 95% confidence interval [CI]: 77.8–80.2%), and that in CYP2C19 extensive metabolizers (EMs), intermediate metabolizer (IMs) and poor metabolizers (PMs) was 77.7% (1,137/1,464, 95% CI: 75.3–79.6%), 81.2% (1,498/1,844, 95% CI: 79.3–83.0%) and 86.8% (644/742, 95% CI: 83.9–88.9%), respectively. Meta-analysis showed that the relative risk of failed eradication in CYP2C19 EMs compared with IMs and PMs was 1.21 (95% CI: 1.06–1.39, P = 0.006) and 1.57 (95% CI: 1.27–1.94, P < 0.001), respectively, in the fixed-effects model. The cure rate of omeprazole and lansoprazole-containing eradication regimens differed among CYP2C19 genotypes (P < 0.05), while that of rabeprazole and esomeprazole-containing regimens was similar. Conclusions: The cure rates of PPI-amoxicillin-clarithromycin H. pylori eradication regimen, especially those containing omeprazole and lansoprazole, differ among CYP2C19 genotypes. Therefore, CYP2C19-dependent tailored treatment may achieve higher eradication rates than standard PPI-amoxicillin-clarithromycin triple regimen.